2014
DOI: 10.3168/jds.2014-8129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of merging levels of locomotion scores for dairy cows on intra- and interrater reliability and agreement

Abstract: Locomotion scores are used for lameness detection in dairy cows. In research, locomotion scores with 5 levels are used most often. Analysis of scores, however, is done after transformation of the original 5-level scale into a 4-, 3-, or 2-level scale to improve reliability and agreement. The objective of this study was to evaluate different ways of merging levels to optimize resolution, reliability, and agreement of locomotion scores for dairy cows. Locomotion scoring was done by using a 5-level scale and 10 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 38 publications
7
37
0
Order By: Relevance
“…Overall, our results are in the range of observers experienced in locomotion scoring (Schlageter-Tello et al, 2014a), who achieved between 60 and 82% of perfect agreement. Alternatively, kappa statistic could also be used for comparisons because it takes into account the agreement by chance for the answers on replicate 1 and 2 (Cohen, 1968).…”
Section: Effect Of Background Educationsupporting
confidence: 51%
See 2 more Smart Citations
“…Overall, our results are in the range of observers experienced in locomotion scoring (Schlageter-Tello et al, 2014a), who achieved between 60 and 82% of perfect agreement. Alternatively, kappa statistic could also be used for comparisons because it takes into account the agreement by chance for the answers on replicate 1 and 2 (Cohen, 1968).…”
Section: Effect Of Background Educationsupporting
confidence: 51%
“…The only practically relevant alternative is to show and assess the same video sample twice. To the best of our knowledge, the largest study assessing within-observer agreement with video included up to 10 experienced observers (Schlageter-Tello et al, 2014a). Therefore, little is known about the within-observer agreement among farmers, students, and veterinarians outside research environments and which factors may influence their performance.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Serving as a reference for model development, Schlageter-Tello et al (2014a) reported that the binary merging level influences the reliability of the locomotion score. The lowest true positive rates were in this study obtained for the lame cows (LS ⩾ 3).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure combines several gait and posture characteristics such as back arch, gait asymmetry and weight bearing into one overall locomotion score (LS) (Sprecher et al, 1997;Flower and Weary, 2009;Schlageter-Tello et al, 2014b). The procedure is however subjective (Schlageter-Tello et al, 2014a), time-consuming and costly. Due to increased farm size and limited time per animal, visual observation of cow health and welfare is evolving to automated monitoring systems.…”
Section: Introductionmentioning
confidence: 99%